Issues surrounding the money laundering crime - Rodrigues, Liliana (Revista Jurídica Portucalense, 2016)
Money laundering took advantage of the increasing openness and expanding markets to improve their techniques, taking advantage of the vulnerability of the weaker countries. In an evolutionary perspective, we understand how this phenomenon has progressed and how countries and referenced organizations have an important role to play in its prevention. This crime was defined and framed in an evolutionary perspective, whether legislative, or jurisprudential doctrine in order to better understand their reason and, consequently, what legal goods to be protected with him. Since this is a complex crime, which has under it a crime that precedes it, there are several different points on relevant issues that prevent a better understanding of the type. Therefore, delineating the subject matter of money laudering to determine whether it is an accessory or, on the contrary, is independent of the underlying crime.